High-Risk Prehospital Mechanisms in Tier II Trauma Codes: An Analysis of Under-Triage at a Level II Trauma Center. Issue 10 (October 2017) - Kozyr, Sergey; Ponce, Santa; Feramisco, Hope; Pakula, Andrea; Skinner, Ruby
Under-triage is used as a surrogate for trauma quality. We sought to analyze factors that may impact under-triage at our institution by a detailed analysis of prehospital mechanisms and patient factors that were associated with the need for invasive intervention, intensive care unit monitoring, or death. Patients admitted to our Level II trauma center who met the criteria for under-triage using the Cribari method were studied, n = 160, and prominent mechanisms were motor vehicle collisions (MVCs). Patient demographics, detailed mechanism characteristics, ED vital signs, operative intervention, and outcomes were studied. The age of the study group and injury severity score were 42 ± 20 and 22 ± 6, respectively. Alcohol or drug use was common as were high-speed frontal collisions. Overall, 38 per cent of patients required surgery, and a monitored bed was required in 60 per cent of patients. Logistic regression identified drug use as predictive of mortality and MVC speeds ≥40 mph as predictive of intensive care unit admission. Patients requiring surgery had a high incidence of frontal collisions, 40 per cent. MVCs were predominant in under-triaged trauma patients. Operative intervention, intensive care unit monitoring, and deaths were associated with frontal impacts, high speeds, and drug use. Further study is warranted to assess the incorporation of high-risk injury patterns in triage algorithms aimed at enhancing trauma quality.